Technology to prevent criminal behavior - De Marco, G; Douglas, T (Oxford University Press, 2021)
This chapter assesses the use of technology to solve social problems such as crime. Starting with a type of education programme that few would find problematic, it details step-by-step a range of interventions that might be offered to rehabilitate offenders. These interventions include a device that not only gives a signal when it detects a precursor of the urge for criminal behaviour, but also releases a drug that is reliably effective at neutralizing these urges. The chapter then presents a view according to which, if we accept the education programme, then we ought to accept all of the other technological interventions. This would mean accepting a greatly expanded role for technology in our criminal justice systems, compared to what we see at present.